VGLUT2 Trafficking Is Differentially Regulated by Adaptor Proteins AP-1 and AP-3 - Li, Haiyan; Santos, Magda S.; Park, Chihyung K.; Dobry, Yuriy; Voglmaier, Susan M. (Frontiers in Cellular Neuroscience, 2017)
Release of the major excitatory neurotransmitter glutamate by synaptic vesicle exocytosis depends on glutamate loading into synaptic vesicles by vesicular glutamate transporters (VGLUTs). The two principal isoforms, VGLUT1 and 2, exhibit a complementary pattern of expression in adult brain that broadly distinguishes cortical (VGLUT1) and subcortical (VGLUT2) systems, and correlates with distinct physiological properties in synapses expressing these isoforms. Differential trafficking of VGLUT1 and 2 has been suggested to underlie their functional diversity. Increasing evidence suggests individual synaptic vesicle proteins use specific sorting signals to engage specialized biochemical mechanisms to regulate their recycling. We observed that VGLUT2 recycles differently in response to high frequency stimulation than VGLUT1. Here we further explore the trafficking of VGLUT2 using a pHluorin-based reporter, VGLUT2-pH. VGLUT2-pH exhibits slower rates of both exocytosis and endocytosis than VGLUT1-pH. VGLUT2-pH recycling is slower than VGLUT1-pH in both hippocampal neurons, which endogenously express mostly VGLUT1, and thalamic neurons, which endogenously express mostly VGLUT2, indicating that protein identity, not synaptic vesicle membrane or neuronal cell type, controls sorting. We characterize sorting signals in the C-terminal dileucine-like motif, which plays a crucial role in VGLUT2 trafficking. Disruption of this motif abolishes synaptic targeting of VGLUT2 and essentially eliminates endocytosis of the transporter. Mutational and biochemical analysis demonstrates that clathrin adaptor proteins (APs) interact with VGLUT2 at the dileucine-like motif. VGLUT2 interacts with AP-2, a well-studied adaptor protein for clathrin mediated endocytosis. In addition, VGLUT2 also interacts with the alternate adaptors, AP-1 and AP-3. VGLUT2 relies on distinct recycling mechanisms from VGLUT1. Abrogation of these differences by pharmacological and molecular inhibition reveals that these mechanisms are dependent on the adaptor proteins AP-1 and AP-3. Further, shRNA-mediated knockdown reveals differential roles for AP-1 and AP-3 in VGLUT2 recycling.